Case Report: Serial Cases: Prolongation of High Immunoglobulin G Level in Repetitive COVID-19 Convalescence Plasma Donor in Saiful Anwar Hospital Malang, Indonesia - Nurarifah, Nina; Brahmantyo, Herwindo Pudjo; Wardhani, Shinta Oktya; Hermanto, Djoko Heri; Arsana, Putu Moda (Frontiers in Immunology, 2021)
Background Convalescent plasma therapy is expected to be a promising alternative to supportive therapy during the SARS-CoV-2 pandemic outbreak. Altered immune response in repetitive convalescent plasma donors has not been widely studied. This case series was reported to analyze the patterns of immune responses and the factors that might influence them in repetitive convalescent plasma donors and increase awareness of COVID-19 survivors to donate their convalescent plasma. Cases Illustration There were five repetitive donors who were eligible as convalescent plasma donor requirements. It was found two donors who showed increment of anti-SARS-CoV-2 IgG level after donation and two others who showed persistent anti-SARS-CoV-2 IgG level more than two months after recovered. Discussion There was a difference in immune response in survivors who have the probability of being exposed to same antigens with survivors who did not, where the group of survivors who are at risk of exposure to antigens after recovery could trigger anamnestic immune response that can increase antiSARS-CoV-2 IgG levels. The other factor that influence the prolongation of anti-SARS-CoV-2 IgG levels are the possibility of neutralizing antibodies in plasma upregulation. Conclusion Immunological phenomenon in SARS-CoV-2, both in survivors and convalescent plasma donors, have not been widely observed and studied. From the case series discussed above, it can be concluded that convalescent plasma donation does not yet have strong evidence of decreasing levels of specific antibodies against SARS-CoV-2 and plasmapheresis procedure is safe to be done without reducing the protective effect of donor antibody post-plasma donation.